Curable composition, heat dissipating material, and article
Patent Information
- Application Number
- JP2024150237
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2024-08-30
- Publication Date
- 2025-03-07
- Estimated Expiration
- 2044-08-30
AI Technical Summary
【0012】 本発明によれば、無機充填剤の分散状態が良好であり、塗工しやすく、適度な可使時間が確保されており、塗工直後の形状保持性が良好であり、室温条件下で硬化させることで、シリコーンを用いなくとも発熱体や放熱器等の表面との密着性に優れているとともに、加熱しても密着性が低下しにくい放熱材を形成することが可能な硬化性組成物を提供することができる。また、本発明によれば、上記の硬化性組成物を硬化させた硬化物である放熱材、及びこの放熱材を用いた物品を提供することができる。
Smart Images

Figure 0007642141000001 
Figure 0007642141000002 
Figure 0007642141000003
Abstract
Description
[Technical field]
[0001] The present invention relates to a curable composition, a heat dissipating material, and an article. [Background technology]
[0002] As integrated circuits become more dense, the amount of heat generated inside electronic devices tends to increase, and there is a demand for the development of technology to efficiently dissipate heat generated inside electronic components. For example, thermal interface materials (TIMs) such as heat dissipation sheets with excellent thermal conductivity are known, which are placed between heat generating bodies such as electronic components installed inside electronic devices and heat sinks and other heat sinks. By using such heat dissipation materials, the minute gaps between the surfaces of the heat generating body and the heat sink can be filled to reduce the contact thermal resistance, allowing the heat from the heat generating body to be transferred appropriately to the heat sink.
[0003] For example, a heat-resistant elastic material has been proposed in which a thermally conductive material is dispersed in a silicone polymer precursor (Patent Document 1). However, there is a strong demand to avoid the use of silicone from the viewpoint of avoiding a decrease in insulation performance due to the generation of low-molecular-weight siloxane, which is a volatile component. For this reason, heat dissipation materials that use non-silicone polymers as binder components and compositions for forming such heat dissipation materials have been studied.
[0004] For example, a thermally conductive polymer molded body has been proposed in which a polymerizable resin composition containing a polymerizable resin component such as polyols and aluminum hydroxide is cured under heating conditions using a curing agent such as isocyanates (Patent Document 2). Also, a thermally conductive cured product has been proposed in which a binder component containing a polyurethane polyurea resin having a carboxy group and a thermally conductive filler is cured under heating conditions using an epoxy compound (Patent Document 3). Furthermore, a silicone-free thermal interface has been proposed in which a component having a reactive functional group such as a polyol and a composition containing a thermally conductive filler are heat-cured (Patent Document 4). [Prior art documents] [Patent documents]
[0005] [Patent Document 1] JP 2005-209955 A [Patent Document 2] Special Publication No. 2015-530470 [Patent Document 3] JP 2020-200454 A [Patent Document 4] JP 2023-508288 A Summary of the Invention [Problem to be solved by the invention]
[0006] However, the conventional compositions proposed in Patent Documents 2 to 4 all require curing under heating conditions, so a heat source must be secured in the device production line. This makes the process of placing the heat dissipation material at the desired location complicated, and there are problems such as the time required for curing, and is not favorable for carbon neutral efforts.
[0007] In addition, since the conventional composition has a relatively high fluidity, it may spread quickly when applied to the target area such as a circuit board including a SUS plate. As a result, the applied shape may not be maintained and the coating may spread to areas where it should not be applied, making it difficult to place the heat dissipation material in the desired location. Furthermore, the adhesion of the cured product such as a heat dissipation material formed using the conventional composition to the target area may easily decrease when heated, and improvement was required.
[0008] The present invention has been made in consideration of the problems of the prior art, and its object is to provide a curable composition that has a good dispersion state of an inorganic filler, is easy to apply, has an appropriate pot life, has good shape retention immediately after application, and is capable of forming a heat dissipation material that has excellent adhesion to the surfaces of heating elements, radiators, etc., even without using silicone, and that is less likely to lose adhesion even when heated, by curing under room temperature conditions. Another object of the present invention is to provide a heat dissipation material that is a cured product obtained by curing the above-mentioned curable composition, and an article using this heat dissipation material. [Means for solving the problem]
[0009] That is, according to the present invention, there is provided the following curable composition. [1] A two-component curing type curable composition containing a combination of a base agent and a curing agent, which is used to form a heat dissipating material, wherein the base agent contains a polyamine (A), a polyol (C), an aminoalcohol (D), and an inorganic filler (E1), the curing agent contains a polyisocyanate (B) and an inorganic filler (E2), the amine value of the polyamine (A) is 300 mgKOH / g or less, the polyol (C) is an amorphous polyol having a side chain branched from the main chain in its molecule, and the aminoalcohol (D) has n units of 1 in its molecule. a compound having a primary amino group and m secondary amino groups (n and m each independently represent 0 or 1, and n+m does not equal 0), a content of the amino alcohol (D) in the total of the polyamine (A), the polyol (C), and the amino alcohol (D) in the main agent is 0.005 to 1 mass%, and a ratio (NCO / (NH+OH)) of the number of moles of isocyanate groups in the curing agent to the total number of moles of amino groups and hydroxyl groups in the main agent (NH+OH) is 0.75 to 2.00. [2] The curable composition according to [1], wherein the content of the polyamine (A) in the base resin is 30 to 90 mass% based on the total of the polyamine (A), the polyol (C), and the amino alcohol (D). [3] The curable composition according to [1] or [2], wherein the polyisocyanate (B) is an aliphatic polyisocyanate. [4] The curable composition according to any one of [1] to [3], wherein the inorganic filler (E1) and the inorganic filler (E2) are each independently at least one selected from the group consisting of metals, metal oxides, metal nitrides, metal hydroxides, and metal carbonates. [5] The curable composition according to any one of [1] to [4], wherein a filling rate of the inorganic filler (E1) in the base agent is 70 to 95 mass %, and a filling rate of the inorganic filler (E2) in the curing agent is 50 to 95 mass %.
[0010] Furthermore, according to the present invention, there is provided the following heat dissipating material. [6] A heat dissipating material which is a cured product obtained by curing the curable composition according to any one of [1] to [5] above. [7] The heat dissipation material according to [6], having a thermal conductivity of 2.0 W / (m K) or more. [8] The heat dissipating material according to the above [6] or [7], wherein a total filling rate of the inorganic filler (E1) and the inorganic filler (E2) is 65 to 95 mass %.
[0011] Further, according to the present invention, there are provided the following articles: [9] An article comprising a heat generating element and the heat dissipation material according to any one of [6] to [8] above, which is placed in contact with the heat generating element. Effect of the Invention
[0012] According to the present invention, it is possible to provide a curable composition that has a good dispersion state of the inorganic filler, is easy to apply, has an appropriate pot life, has good shape retention immediately after application, and is capable of forming a heat dissipation material that has excellent adhesion to the surfaces of heating elements, radiators, etc., even without using silicone, and that is resistant to deterioration in adhesion even when heated, by curing under room temperature conditions. Also, according to the present invention, it is possible to provide a heat dissipation material that is a cured product obtained by curing the above-mentioned curable composition, and an article using this heat dissipation material. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0013] <Curable composition> Hereinafter, the embodiment of the present invention will be described, but the present invention is not limited to the following embodiment. One embodiment of the curable composition of the present invention is a two-part curing type curable composition containing a combination of a base agent and a curing agent used to form a heat dissipation material. The base agent contains polyamine (A), polyol (C), aminoalcohol (D), and inorganic filler (E1), and the curing agent (hereinafter also referred to as "B liquid" or "second agent") contains polyisocyanate (B) and inorganic filler (E2). The amine value of the polyamine (A) is 300 mg KOH / g or less, and the polyol (C) is an amorphous polyol having a side chain branched from the main chain in its molecule. The aminoalcohol (D) is a compound having n primary amino groups and m secondary amino groups in its molecule (n and m each independently represent 0 or 1, and n+m=0 does not occur). The content of the amino alcohol (D) in the total of the polyamine (A), polyol (C), and amino alcohol (D) in the base is 0.005 to 1 mass %. The ratio (NCO / (NH+OH)) of the number of moles of isocyanate groups (NCO) in the curing agent to the total number of moles of amino groups and hydroxyl groups (NH+OH) in the base is 0.75 to 2.00. The curable composition of this embodiment will be described in detail below.
[0014] (Main agent (liquid A)) The curable composition of this embodiment is a two-part curing composition containing a combination of a main agent and a curing agent, and is a composition set of the type in which the two parts (two components) are mixed and then cured under a predetermined condition. The main agent (hereinafter also referred to as "liquid A" or "first agent") contains polyamine (A), polyol (C), aminoalcohol (D), and inorganic filler (E1), and is preferably a composition substantially composed of only polyamine (A), polyol (C), aminoalcohol (D), and inorganic filler (E1). It is preferable that the main agent is a solvent-free composition that does not substantially contain a liquid medium.
[0015] Polyamine (A) is a component having two or more amino groups in its molecule, which reacts with polyisocyanate (B) in the curing agent to form a urea bond. The amino groups in polyamine (A) and amino alcohol (D) react faster with the isocyanate groups in polyisocyanate (B) than the hydroxyl groups in polyol (C). Therefore, by using polyamine (A) and amino alcohol (D), urea bonds are quickly formed, shape retention and adhesion can be achieved immediately after coating, and a heat dissipation material in which the decrease in adhesion due to heating is suppressed can be formed.
[0016] The polyamine (A) also functions as a dispersant to disperse the inorganic filler (E1) uniformly in the base resin in a good condition. Therefore, by using the polyamine (A), it is possible to increase the filling rate (content) of the inorganic filler (E1), and form a heat dissipation material that is a cured product with excellent thermal conductivity and less unevenness in physical properties such as thermal conductivity and adhesion.
[0017] When a base material containing a dispersant (excluding polyamine (A)) that disperses inorganic fillers is used, the dispersant may bleed out from the heat dissipating material formed, which may lead to a decrease in the adhesion of the heat dissipating material. In contrast, polyamine (A), which can also function as a dispersant, is incorporated into the molecules of the polymer (polyurethane polyurea resin) by reacting with polyisocyanate (B), so it does not bleed out from the heat dissipating material formed. For this reason, by using a base material that does not substantially contain a dispersant (excluding polyamine (A)) that disperses inorganic fillers (E1), it is expected that the dispersant will not bleed out from the heat dissipating material formed, and a heat dissipating material in which the decrease in adhesion over time is suppressed can be formed.
[0018] The amine value of the polyamine (A) is 300 mgKOH / g or less, preferably 20 to 250 mgKOH / g, and more preferably 70 to 200 mgKOH / g. The polyamine (A) with an amine value of more than 300 mgKOH / g has a small molecule and therefore tends to have a high reaction rate. Therefore, it is prone to heat generation during curing and the pot life is short.
[0019] The base agent may contain two or more polyamines (A). When the base agent contains two or more polyamines (A), the "amine value of the polyamine (A)" is the maximum value (maximum amine value) among the amine values of the two or more polyamines.
[0020] The polyol (C) is a component having two or more hydroxyl groups in its molecule, which reacts with the polyisocyanate (B) in the curing agent to form a urethane bond. The hydroxyl groups in the polyol (C) and aminoalcohol (D) react slower with the isocyanate groups in the polyisocyanate (B) than the amino groups in the polyamine (A). Therefore, by using the polyamine (A), polyol (C), and aminoalcohol (D) in combination, after the urea bond is quickly formed and the initial physical properties are expressed, the remaining polyisocyanate (B) reacts gently with the polyol (C) and aminoalcohol (D) to form a urethane bond, so that a heat dissipation material having excellent adhesion and suppressed deterioration of adhesion due to heating can be formed while ensuring moderate fluidity and sufficient pot life.
[0021] The polyol (C) is an amorphous polyol having a side chain branched from the main chain in its molecule. When an amorphous polyol having a side chain is used, the side chain interacts with the inorganic filler, improving the dispersibility of the inorganic filler. This makes it possible to obtain a curable composition that has a relatively low viscosity and is easier to use as a coating material. In contrast, when a crystalline polyol having no side chain, an amorphous polyol having no side chain, or a crystalline polyol having a side chain is used, the fluidity of the base agent (liquid A) decreases and it becomes difficult to ensure a sufficient pot life.
[0022] Examples of amorphous polyols having side chains branched from the main chain in the molecule include short-chain diols such as 1,2-propylene glycol, 1,3-butylene glycol, 2-methylpropanediol, 3-methylpentanediol, 1,2-butanediol, and 1,2-hexanediol; polyester-based diols containing structural units derived from diols having branched alkyl chains such as neopentanediol, 2-methyl-1,3-propanediol, 3-methyl-1,5-pentanediol, 2,4-diethyl-1,5-pentanediol, and 2-butyl-2-ethyl-1,3-propanediol; polycarbonate-based diols; polyether-based diols such as polypropylene glycol; polybutadiene polyols, etc. In particular, castor oil polyols are preferred because they have a relatively low viscosity and a long-chain side chain in the molecule.
[0023] The hydroxyl value of the polyol (C) is not particularly limited, and is usually 50 to 1,500 mgKOH / g. From the viewpoint of adjusting the reaction rate and pot life, it is preferably 80 to 1,250 mgKOH / g, and more preferably 100 to 600 mgKOH / g. If the hydroxyl value of the polyol (C) is too low, the reaction rate at room temperature tends to be slow, and it may be difficult to ensure normal adhesion. On the other hand, if the hydroxyl value of the polyol (C) is too high, the reaction rate at room temperature tends to be too fast, and the pot life may be shortened.
[0024] The amino alcohol (D) is a compound having n primary amino groups (-NH2) and m secondary amino groups (-NH-) (n and m are each independently 0 or 1, and n+m does not equal 0) in its molecule, and is a component that reacts with the polyisocyanate (B) in the curing agent to form a urea bond, similar to the polyamine (A). By using such an amino alcohol (D) in combination with the polyamine (A), as described above, it is possible to quickly form a urea bond, and to develop shape retention and adhesion immediately after coating, and to form a heat dissipation material in which the decrease in adhesion due to heating is suppressed. On the other hand, if an amino alcohol having two or more primary amino groups (-NH2) in its molecule or an amino alcohol having only a tertiary amino group in its molecule (n+m=0) is used, it becomes difficult to obtain the desired properties (adhesion, shape retention, appropriate pot life).
[0025] The amino alcohol (D) is preferably a compound having one secondary amino group and one or two hydroxyl groups in its molecule (however, the number of primary amino groups (n) is 0). By using such an amino alcohol (D), a more sufficient pot life can be ensured. If more rapid curing is desired, the amino alcohol (D) is preferably a compound having one primary amino group in its molecule (however, the number of secondary amino groups (m) is 0 or 1).
[0026] Examples of the amino alcohol (D) include N-methylethanolamine, 2-ethylaminoethanol, mono-n-butylethanolamine, 3-methylamino-1,2-propanediol, monoethanolamine, diethanolamine, and N-(β-aminoethyl)ethanolamine.
[0027] In the base resin, the content of the amino alcohol (D) in the total of the polyamine (A), polyol (C), and amino alcohol (D) is 0.005 to 1 mass%, preferably 0.01 to 0.5 mass%, and more preferably 0.01 to 0.3 mass%. If the content of the amino alcohol (D) in the total of the polyamine (A), polyol (C), and amino alcohol (D) is less than 0.005 mass%, the shape retention immediately after coating may be poor, or the adhesion may decrease when heated. On the other hand, if the content of the amino alcohol (D) in the total of the polyamine (A), polyol (C), and amino alcohol (D) is more than 1 mass%, the curing speed becomes too fast, and the pot life becomes insufficient.
[0028] In the base resin, the content of polyamine (A) in the total of polyamine (A), polyol (C), and aminoalcohol (D) is preferably 30 to 90 mass%, more preferably 35 to 85 mass%, and particularly preferably 40 to 60 mass%. If the content of polyamine (A) in the total of polyamine (A), polyol (C), and aminoalcohol (D) is less than 30 mass%, curing may be somewhat difficult under room temperature (25°C) conditions, or the curing time may be somewhat long. On the other hand, if the content of polyamine (A) in the total of polyamine (A), polyol (C), and aminoalcohol (D) is more than 90 mass%, the curing speed may be somewhat fast and the usable time may be somewhat short.
[0029] The inorganic filler (E1) in the base agent and the inorganic filler (E2) in the curing agent are both inorganic components having thermal conductivity. That is, the base agent and the curing agent constituting the curing composition of the present embodiment both contain an inorganic filler. By making both the base agent and the curing agent contain an inorganic filler, the base agent and the curing agent can be mixed uniformly, and a heat dissipation material can be formed, which is a cured product in which the inorganic filler is uniformly dispersed.
[0030] The inorganic filler (E1) in the base agent and the inorganic filler (E2) in the curing agent may be the same type or different types. The base agent contains a polyamine (A) that can also function as a dispersant. For this reason, the base agent can be filled (contained) with a relatively large amount of the inorganic filler (E1). Specifically, the filling rate of the inorganic filler (E1) in the base agent is preferably 70 to 95 mass%, more preferably 80 to 95 mass%. The filling rate of the inorganic filler (E2) in the curing agent is preferably 50 to 95 mass%, more preferably 85 to 90 mass%.
[0031] The inorganic filler (E1) and the inorganic filler (E2) are preferably at least one selected from the group consisting of metals, metal oxides, metal nitrides, metal hydroxides, and metal carbonates. Examples of metals include gold, silver, copper, aluminum, and alloys containing these. Examples of metal oxides include alumina, calcium oxide, magnesium oxide, zinc oxide, beryllia, titanium oxide, and silica. Examples of metal nitrides include aluminum nitride, boron nitride, carbon nitride, and silicon nitride. Examples of metal hydroxides include aluminum hydroxide, magnesium hydroxide, and calcium hydroxide. Examples of metal carbonates include calcium carbonate, magnesium carbonate, and hydrotalcite. The inorganic fillers can be used alone or in combination of two or more.
[0032] Examples of the particle shape of the inorganic filler (E1) and the inorganic filler (E2) include spherical, acicular, flaky, dendritic, fibrous, and amorphous. The average particle size of the inorganic filler (E1) and the inorganic filler (E2) is not particularly limited, and may be within the range of, for example, 0.1 to 100 μm. In this specification, the term "average particle size" refers to the cumulative 50% particle size (median size; D) on a volume basis measured by a laser diffraction scattering method. 50 ).
[0033] (Hardening agent (liquid B)) The curing agent (hereinafter also referred to as "liquid B" or "second agent") contains polyisocyanate (B) and inorganic filler (E2), and is preferably a composition substantially composed of only polyisocyanate (B) and inorganic filler (E2). Therefore, this curing agent reacts quickly with hydroxyl groups and amino groups in the base resin. The curing agent is preferably a solvent-free composition that does not substantially contain a liquid medium.
[0034] The polyisocyanate (B) is a compound having two or more isocyanate groups in its molecule. Examples of the polyisocyanate (B) include aliphatic polyisocyanates, aromatic polyisocyanates, and alicyclic polyisocyanates. The aliphatic polyisocyanates include modified aliphatic polyisocyanates.
[0035] Aliphatic polyisocyanates include 1,4-tetramethylene diisocyanate, 1,6-hexamethylene diisocyanate (HDI), and 1,10-decamethylene diisocyanate.
[0036] Examples of aromatic polyisocyanates include 4,4'-diphenylmethane diisocyanate (MDI), 2,2'-MDI, 2,4'-MDI, polymeric MDI, 2,4-tolylene diisocyanate (TDI), 2,6-TDI, m-xylylene diisocyanate (XDI), 1,4-phenylene diisocyanate, 4-methoxy-1,3-phenylene diisocyanate, 4-isopropyl-1,3-phenylene diisocyanate, 4-butoxy-1,3-phenylene diisocyanate, 2,4-diisocyanate diphenyl ether, 1,5-naphthalene diisocyanate, and benzidine diisocyanate.
[0037] Examples of the modified aliphatic polyisocyanate include an isocyanurate, allophanate, biuret, and adduct of an aliphatic polyisocyanate with a polyol (eg, trimethylolpropane).
[0038] The polyisocyanate (B) is preferably an aliphatic polyisocyanate. The aliphatic polyisocyanate has a slower reaction rate with the polyol (C) than the aromatic polyisocyanate. Therefore, by using the aliphatic polyisocyanate, the pot life of the curable composition can be more sufficiently secured. It is also preferable to use the aliphatic polyisocyanate and the aromatic polyisocyanate in combination to adjust the pot life.
[0039] Moreover, the polyisocyanate (B) is more preferably an aliphatic polyisocyanate modified product, and among the aliphatic polyisocyanate modified products, the nurate type is particularly preferred. By using the aliphatic polyisocyanate modified product, a heat dissipating material that is a three-dimensional cured product can be formed. That is, even when cured under room temperature conditions, a heat dissipating material that is a cured product with improved room temperature adhesion can be formed.
[0040] The curing agent contains a polyisocyanate (B) that is somewhat highly reactive. For this reason, it is preferable to use an inorganic filler (E2) that is less reactive with the polyisocyanate (B). For example, a metal oxide or metal nitride can be used as the inorganic filler (E2) in the curing agent, and a metal hydroxide or metal carbonate can be used as the inorganic filler (E1) in the base resin.
[0041] The ratio (NCO / (NH+OH)) of the number of moles (NCO) of isocyanate groups in the curing agent to the total number of moles (NH+OH) of amino groups and hydroxyl groups in the base agent is 0.75 to 2.00, preferably 1.00 to 1.95, and more preferably 1.75 to 1.90. By setting the value of "NCO / (NH+OH)" within the above range, it is possible to obtain a room temperature curing type curing composition that can form a heat dissipating material that has excellent adhesion and is not easily reduced in adhesion even by heating while ensuring a moderate pot life. Note that the content of amino alcohol (D) is extremely small, so the "total number of moles (NH+OH) of amino groups and hydroxyl groups in the base agent" does not include the amino groups and hydroxyl groups of the amino alcohol (D).
[0042] (Other Ingredients) Various additives can be added to the curable composition of the present embodiment as necessary. Examples of additives include coupling agents for improving substrate adhesion, ion trapping agents for improving insulation reliability during moisture absorption, various dispersants, and leveling agents. The curable composition of the present embodiment is preferably a so-called silicone-free composition that does not substantially contain silicone. The curable composition of the present embodiment can form a heat dissipation material that has excellent adhesion to the surface of a heating element, a heat sink, etc., even without using silicone.
[0043] (Method of producing curable composition) The above-mentioned components can be mixed in a conventional manner to obtain the main agent and the curing agent, respectively. The main agent and the curing agent thus obtained can then be appropriately combined to obtain the desired two-part curing type curable composition.
[0044] The viscosity of the base agent and the curing agent at 20°C is preferably 100 to 1,000 Pa·s, respectively. If the viscosity is less than 100 Pa·s, the inorganic filler may be more likely to settle, and the storage stability may be slightly reduced. On the other hand, if the viscosity is more than 1,000 Pa·s, the discharge pressure during coating may be excessively high, and problems may easily occur in practical use. In consideration of storage stability and suitability for use of coating, the viscosity of the base agent and the curing agent at 20°C is more preferably 200 to 750 Pa·s, respectively. In addition, if the viscosity of the base agent at 20°C is 300 to 750 Pa·s and the viscosity of the curing agent at 20°C is 200 to 550 Pa·s, the viscosity difference between these two agents is relatively small, making them easier to mix, which is particularly preferable in terms of suitability for use.
[0045] <Heat dissipation material> One embodiment of the heat dissipating material of the present invention is a cured product obtained by curing the above-mentioned curable composition. After mixing the main agent and the curing agent constituting the curable composition, the mixture is applied to the surface of a heat generating body such as a heat generating electronic component or a heat sink or other heat dissipating device according to a conventional method. Thereafter, the mixture is cured by holding it at room temperature (about 25°C) for a predetermined time without heating, and the desired heat dissipating material can be formed at a desired location. The time required for curing can be set by appropriately adjusting the content of the amino alcohol (D) in the total of the polyamine (A), polyol (C), and amino alcohol (D) in the main agent, and the ratio (NCO / (NH+OH)) of the number of moles of isocyanate groups (NCO) in the curing agent to the total number of moles of amino groups and hydroxyl groups (NH+OH) in the main agent. Specifically, the mixture can be cured by holding it for about 6 to 48 hours.
[0046] Since the curable composition is a composition that can be cured at room temperature, even when it is formed on the surface of a heat-sensitive member (such as a CPU), it can be cured without substantially damaging such a member to form the intended heat dissipation material. The thermal conductivity of the heat dissipation material thus formed is usually 2.0 W / (m·K) or more, preferably 2.5 W / (m·K) or more, and more preferably 2.5 to 4.0 W / (m·K). The total filling rate of the inorganic filler (E1) and the inorganic filler (E2) in the heat dissipation material thus formed is preferably 65 to 95 mass%. For this reason, the heat dissipation material of this embodiment is useful as a heat dissipation material (TIM) such as a heat dissipation sheet arranged between a heat generating body such as a heat generating electronic component provided inside an electronic device and a heat sink or other heat dissipator.
[0047] In order to apply a two-component curing type curable composition to a desired location, for example, it is preferable to use a static mixer (dispenser) for mixing two components (two liquids) in a flow path and a nozzle capable of discharging a liquid mixture of the two components, which is a curable composition, from the tip, and extrude the curable composition from the tip of the nozzle while mixing the two liquids (main agent and curing agent). The above-mentioned curable composition has a sufficient pot life, and even if the main agent and the curing agent are mixed, they do not immediately harden under room temperature conditions, and can be easily applied to a desired location. In addition, since the above-mentioned curable composition has good shape retention immediately after application, it can be accurately applied to a desired location. Furthermore, since the curable composition can be extruded from the tip of a thin nozzle while ensuring the pot life, it can be injected into a narrow gap (gap) between members, and is highly versatile. In addition, the heat dissipation material of this embodiment has excellent adhesion to various substrate surfaces, does not easily peel off from the substrate surface, etc. even when heated, and has excellent heat-resistant adhesion.
[0048] <Goods> One embodiment of the article of the present invention includes a heat generating body and the above-mentioned heat dissipation material arranged in contact with the heat generating body. Examples of the heat generating body include various circuit boards and electronic components such as semiconductor devices. Examples of the semiconductor device include power modules such as power semiconductor devices, LEDs, and inverter devices. The semiconductor device is equipped with, for example, semiconductor elements such as insulated gate bipolar transistors, diodes, and IC chips; and various heat generating elements such as resistors and capacitors.
[0049] Even if the heat dissipation material is silicone-free, it has excellent adhesion to the surfaces of heat generating bodies and heat sinks, and has high thermal conductivity. In addition, since the heat dissipation material can be formed under room temperature conditions, it is suitable for use on heat generating bodies such as electronic components that are sensitive to heat. Since the heat dissipation material has excellent heat-resistant adhesion, it will not easily peel off due to the heat of the heat generating body even if it is placed in contact with the heat generating body. EXAMPLES
[0050] Hereinafter, the present invention will be specifically described based on examples, but the present invention is not limited to these examples. In addition, "parts" and "%" in the examples and comparative examples are based on mass unless otherwise specified.
[0051] <Preparation of Materials> Various materials shown in Tables 1 to 3 were prepared. In Table 2, "OH1", "OH2", and "OH3" are all amorphous polyols having side chains branched from the main chain (having a branched structure) in their molecules. "OH1" and "OH2" are castor oil polyols, "OH3" is a polyester diol containing structural units derived from 3-methyl-1,5-pentanediol, and "OH4" is a polyester polyol composed of 1,4-butanediol and adipic acid. Also, "NCO1" and "NCO2" are both aliphatic polyisocyanates (aliphatic polyisocyanate modified products (nurate forms)), and "NCO3" is polymeric MDI.
[0052] In Table 2, "ADD1" to "ADD9" are all commercially available as pigment dispersants. Further, in Table 3, the particle shapes of "filler9 to 14" are all spherical, "filler7" is irregular in shape, and "filler8" is flaky.
[0053] TIFF0007642141000001.tif84170
[0054] TIFF0007642141000002.tif136170
[0055] TIFF0007642141000003.tif166170
[0056] <Preparation of Liquid A (Main Agent)> (Liquid A A-1) A mixing container equipped with a stirrer, a reflux condenser, a thermometer, a nitrogen injection tube, and a manhole was prepared. While replacing the inside of this mixing container with nitrogen gas, 50 parts of OH1, 49.99 parts of NH1, and 0.01 parts of ON1 were put in. After dehydration treatment by heating under reduced pressure, it was stirred at 100 °C for 1 hour under a nitrogen stream to make it uniform, and a resin component for the main agent was obtained. 100 parts of the obtained resin component for the main agent, 600 parts of filer2, 300 parts of filer3, and 100 parts of filer4 were mixed and stirred using a stirring mixer (trade name "Awatori Ren Taro", manufactured by Shinky Co., Ltd.) for 5 minutes to obtain A liquid A-1 which is the main agent.
[0057] (Liquid A A-2 to A-45) Except for using each component of the types and amounts (unit: parts) shown in the upper rows of Tables 4-1 to 4-4, in the same manner as in the case of Liquid A A-1 described above, Liquid A A-2 to A-45 which are the main agents were obtained. The "filling ratio (mass%)" and "filling ratio (volume%)" in Tables 4-1 to 4-4 are the ratios of the inorganic filler in the main agent (Liquid A).
[0058] TIFF0007642141000004.tif153170
[0059] TIFF0007642141000005.tif180170
[0060] TIFF0007642141000006.tif183170
[0061] TIFF0007642141000007.tif196170
[0062] <Preparation of Liquid B (Hardener)> (Liquid B B-1) 50 parts of NCO1, 50 parts of NCO2, 550 parts of filer2, 200 parts of filer3, and 150 parts of filer4 were mixed and stirred using a stirring mixer (trade name "Awatori Ren Taro", manufactured by Shinky Co., Ltd.) for 5 minutes to obtain Liquid B B-1 which is the hardener.
[0063] (Liquid B B-2 to B-45) Except for using the types and amounts (units: parts) of each component shown in the upper rows of Tables 5-1 to 5-4, hardeners B-2 to B-45 were obtained in the same manner as for the above-mentioned B-1 solution. The "filling rate (mass%)" and "filling rate (volume%)" in Tables 5-1 to 5-4 are the proportions of inorganic filler in the hardener (B solution).
[0064] TIFF0007642141000008.tif95170
[0065] TIFF0007642141000009.tif146170
[0066] TIFF0007642141000010.tif157170
[0067] TIFF0007642141000011.tif142170
[0068] <Preparation of paint (curable composition)>
[0069] Paints (two-component curing type curable compositions) were prepared by combining the types of liquid A and liquid B shown in Tables 6-1 to 6-4 in a mass ratio of 1:1. The "filling rate (mass%)" and "filling rate (volume%)" in Tables 6-1 to 6-4 are the proportions of inorganic filler in the entire curable composition (the sum of liquid A and liquid B).
[0070] In addition, a dispenser gun with a discharge trigger, a dispenser for mixing two liquids, and a cylindrical static mixer were prepared. Inside the dispenser, a partition wall was provided along the flow direction to separate the two liquids (two agents). The dispenser gun was connected to the base of the dispenser in the flow direction, and the base of the static mixer was connected to the tip of the dispenser in the flow direction. When the trigger of the dispenser gun was pulled, the two liquids contained inside the dispenser were pushed out from the tip of the dispenser and flowed into the static mixer. The two liquids that flowed into the static mixer were mixed evenly while flowing, and were discharged from the tip of the static mixer.
[0071] <Evaluation of Paint (Curable Composition)> (Liquidity) Each paint (liquid A and liquid B) taken out of the stirring mixer was placed in a separate container. Liquid A was colored by adding 1% by mass of a blue coloring material (product name "Cyanine Blue ZC-7925_T_10_2", manufactured by Dainichiseika Chemicals Co., Ltd.) that does not affect the fluidity. The container was tilted or scraped out with a spatula, and liquid A and liquid B were poured into the prepared dispenser, respectively, and then a dispenser gun and a static mixer were connected to the base and tip of the dispenser, respectively. The trigger of the dispenser gun was pulled to discharge the paint (curable composition) from the tip of the static mixer, and the fluidity of the paint (liquid A and liquid B) was evaluated according to the evaluation criteria shown below. Since liquid A was colored blue, when only liquid A did not flow, a white paint was discharged, when only liquid B did not flow, a blue paint was discharged, and when both liquid A and liquid B flowed, a light blue paint was discharged. In other words, the fluidity of each of liquid A and liquid B can be evaluated by checking the color of the discharged paint. The results are shown in Tables 6-1 to 6-4. ◎: When pouring into the dispenser, the container was tilted 180° to allow easy flow. ○: Discharge was possible easily by simply pulling the trigger lightly. △: The trigger was difficult to pull, but it was possible to dispense the medicine. ×: Discharge was impossible.
[0072] (Pot life) Each paint (combination of liquid A and liquid B) was placed in a dispenser. The trigger of the dispenser gun was pulled to discharge the paint from the tip of the static mixer, and the paint was then left for a specified time. The pot life was determined as the time it was left until it hardened at the tip of the static mixer and could not be discharged again. The pot life was evaluated according to the following evaluation criteria. With this dispenser, it is assumed that the contents will be replaced within one hour, and if a large amount is used, the contents can be used up in 30 minutes. The results are shown in Tables 6-1 to 6-4. ◎: Usable for more than 3 hours. ○: Usable for 1 hour or more but less than 3 hours. △: Usable for 30 minutes or more but less than 1 hour. ×: Unusable within 30 minutes.
[0073] (shape retention) Each paint (combination of liquid A and liquid B) was placed in a dispenser. The trigger of the dispenser gun was pulled to eject the paint from the tip of the static mixer and apply it to the target area of the SUS plate, and the paint was left for 1 minute at room temperature of 25°C. After leaving the paint, the coated product was visually observed and its shape retention was evaluated according to the following evaluation criteria. The results are shown in Tables 6-1 to 6-4. ○: No change (the shape of the coating was maintained on the target area) ×: Change occurred (the coating spread from the target area)
[0074] (Normal close contact) Each paint (combination of liquid A and liquid B) was placed in a dispenser. The trigger of the dispenser gun was pulled to eject the paint from the tip of the static mixer and apply it to a SUS plate, and a test piece was made by bonding two SUS plates together. The test piece was left at room temperature (25°C) for one day, after which the two SUS plates were peeled off with bare hands and the normal adhesion was evaluated according to the evaluation criteria shown below. The results are shown in Tables 6-1 to 6-4. : No peeling occurred. ◯: Interfacial peeling occurred. △: Cohesive failure occurred. ×: Uncured (liquid or syrup-like).
[0075] (Heat-resistant adhesion) The test pieces prepared for the evaluation of "normal adhesion" were heat-treated at 120°C for 30 minutes, and the heat-resistant adhesion was evaluated according to the following evaluation criteria. The results are shown in Tables 6-1 to 6-4. ○: No peeling occurred. ×: Peeled off.
[0076] (Thermal Conductivity) The thermal conductivity of the cured product obtained by curing the coating material (curable composition) was measured by the hot disk method (ISO 22007-2). Specifically, the coating material was applied to a mold (10 cm x 10 cm) and then pressed at a constant pressure. The coating material was then aged at 40°C for 96 hours to obtain a film-like cured product. The thermal conductivity of the obtained cured product (heat dissipating material) was then measured using a thermal property measuring device (product name "TPS2500S", manufactured by Kyoto Electronics Manufacturing Co., Ltd.). The results are shown in Tables 6-1 to 6-4.
[0077] TIFF0007642141000012.tif135170
[0078] TIFF0007642141000013.tif136170
[0079] TIFF0007642141000014.tif116170
[0080] TIFF0007642141000015.tif116170 [Industrial Applicability]
[0081] The curable composition of the present invention is useful as a material for forming a heat dissipating material such as a heat dissipating sheet to be placed between a heat generating body such as an electronic component and a heat dissipating device such as a heat sink.
Claims
1. A two-part curing type curable composition used to form a heat dissipation material, comprising a combination of a base agent and a curing agent, The base material contains a polyamine (A), a polyol (C), an aminoalcohol (D), and an inorganic filler (E1), The curing agent contains a polyisocyanate (B) and an inorganic filler (E2), The amine value of the polyamine (A) is 300 mgKOH / g or less, the polyol (C) is an amorphous polyol having a side chain branched from a main chain in the molecule, the amino alcohol (D) is a compound having n primary amino groups and m secondary amino groups in the molecule (n and m each independently represent 0 or 1, and n+m does not equal 0); the content of the amino alcohol (D) in the base resin relative to the total content of the polyamine (A), the polyol (C), and the amino alcohol (D) is 0.005 to 1 mass %, The curable composition has a ratio (NCO / (NH+OH)) of the number of moles (NCO) of isocyanate groups in the curing agent to the total number of moles (NH+OH) of amino groups and hydroxyl groups in the base agent of 0.75 to 2.
00.
2. The curable composition according to claim 1, wherein the content of the polyamine (A) in the base resin is 30 to 90 mass% based on the total of the polyamine (A), the polyol (C), and the amino alcohol (D).
3. The curable composition according to claim 1 , wherein the polyisocyanate (B) is an aliphatic polyisocyanate.
4. The curable composition according to claim 1, wherein the inorganic filler (E1) and the inorganic filler (E2) are each independently at least one selected from the group consisting of a metal, a metal oxide, a metal nitride, a metal hydroxide, and a metal carbonate.
5. The filling rate of the inorganic filler (E1) in the base material is 70 to 95 mass %, The curable composition according to claim 1, wherein the filling rate of the inorganic filler (E2) in the curing agent is 50 to 95 mass %.
6. A heat dissipating material which is a cured product obtained by curing the curable composition according to any one of claims 1 to 5.
7. The heat dissipation material according to claim 6, having a thermal conductivity of 2.0 W / (m·K) or more.
8. The heat dissipation material according to claim 6, wherein the total filling rate of the inorganic filler (E1) and the inorganic filler (E2) is 65 to 95 mass%.
9. A heating element; An article comprising the heat dissipation material according to claim 6 , which is placed in contact with the heat generating element.
Citation Information
Patent Citations
Aqueous polyurethane resin composition and laminated film
JP2005139435A
Heat-resistant elastic material
JP2005209955A
Sheet for building material using aqueous adhesive, and its manufacturing method
JP2009084836A
Thermally conductive polymers and resin compositions for producing them
JP2015530470A
Thermosetting resin composition for thermal conductive material and cured product of the same, electronic component and electronic apparatus
JP2020200454A